Emerging Roles for Eph Receptors and Ephrin Ligands in Immunity - Darling, Thayer K.; Lamb, Tracey J. (Frontiers in Immunology, 2019)
Eph receptors are the largest family of receptor tyrosine kinases and mediate a myriad of essential processes in humans from embryonic development to adult tissue homeostasis through interactions with membrane-bound ephrin ligands. The ubiquitous expression of Eph receptors and ephrin ligands among the cellular players of the immune system underscores the importance of these molecules in orchestrating an optimal immune response. This review provides an overview of the various roles of Eph receptors and ephrin ligands in immune cell development, activation, and migration. We also discuss the role of Eph receptors in disease pathogenesis as well as the implications of Eph receptors as future immunotherapy targets. Given the diverse and critical roles of Eph receptors and ephrin ligands throughout the immune system during both resting and activated states, this review aims to highlight the critical yet underappreciated roles of this family of signaling molecules in the immune system.